Mixed Results on the Efficacy of the CharacterMe Smartphone App to Improve Self-Control, Patience, and Emotional Regulation Competencies in Adolescents - Schnitker, Sarah A.; Shubert, Jennifer; Ratchford, Juliette L.; Lumpkin, Matt; Houltberg, Benjamin J. (Frontiers in Psychology, 2021)
Unprecedented levels of access to adolescents' time and attention provide opportunities to convert traditional socioemotional learning into behavioral intervention technologies, but these new tools must be evaluated rather than assuming previously validated activities will be efficacious when converted to a mobile platform. Thus, we sought to provide initial data on the effectiveness of the CharacterMe smartphone app to build self-control, patience, and emotion regulation in a sample of 618 adolescents (Mage = 16.07, Female = 56.6%). We also sought to examine whether framing the app activities as having a transcendent (spiritual connection or moral/prosocial) rather than instrumental purpose would increase engagement and change in self-control, patience, and emotion regulation. Finally, we tested the impact of framing activities as building strengths versus fixing weakness. Results highlight the difficulty of translating psychological interventions to behavioral intervention technologies. Overall, the CharacterMe smartphone app was unsuccessful in increasing self-control, patience, or emotion regulation in adolescents with analyses showing no significant mean changes over time. Framing conditions and user engagement were largely not significant predictors of change in self-control, patience, and emotion regulation.